A size, shape and concentration controlled self-assembling structure with host–guest recognition at the liquid–solid interface studied by STM. Issue 23 (31st May 2016) - Shen, Mengqi; Luo, Zhouyang; Zhang, Siqi; Wang, Shuai; Cao, Lili; Geng, Yanfang; Deng, Ke; Zhao, Dahui; Duan, Wubiao; Zeng, Qingdao
Abstract : Here we reported the fabrication of host networks formed by two newly prepared phenanthrene-butadiynylene macrocycles (PBMs) at the liquid–solid interface. Abstract : In the present investigation, we reported the fabrication of host networks formed by two newly prepared phenanthrene-butadiynylene macrocycles (PBMs) at the liquid–solid interface. Size, shape and concentration controlled experiments have been performed to investigate the PBMs/coronene (COR) host–guest system with the structural polymorphism phenomenon. Initially, PBM1 could form a regular linear network structure and PBM2 form a well-ordered nanoporous network structure. When the COR molecules were introduced, the self-assembled structure of PBM1 remained unchanged, while COR could be entrapped into the cavities of the PBM2 nanoporous network, and the co-assembly of the PBM2/COR host–guest systems underwent a structural transformation with the increase of concentration of COR. Scanning tunneling microscopy (STM) measurements and density functional theory (DFT) calculations are utilized to reveal the formation mechanism of the molecular nanoarrays controlled by the solution concentration.